Artificial Intelegence Pemanfaatan Metode Hill Climbing Mencari Lintasan Terpendek Objek Wisata Menggunakan sistem Informasi - Sestri Novia Rizki; Yopy Mardiansyah (STEKOM PRESS, 2021)
The search is often used to search for the shortest route, the Hill Climbing Method is a part of the test that uses heuristic functions. The problem that is often encountered is in the form of miscalculations in calculating the distance so that it requires long distances, costs a lot and takes a very long time. To solve this case, it can be solved by making a structure graph by looking at the city points from the two sides of the point to be passed. Using an algorithm can help make it easier to find a location and save time and travel costs that will be passed. This advantage is that all points will be obtained and checked from the right and left sides one by one so as to obtain effective and maximum results. The Hill Climbing method that will be used has the concept of a geographic information system as a guide and is used as a system for decision making. The heuristic search method is one of the methods commonly used in finding a way